Some results for generalized cauchy numbers - Zhao, Feng-Zhen (Utilitas Mathematica, 2010)
In this paper, we study the properties of the generalized Cauchy numbers. Using the method of coefficient, we establish some identities related to the generalized Cauchy numbers and extend some recurrence relations for Cauchy numbers. We further give some asymptotic expansions of certain sums involving these numbers.